The Roles Of Price and Services in Increasing Customer Satisfaction at Culinary Business in Berastagi, Regency of Karo - Syahrul (Tourism, Hospitality And Culture Insights Journal, 2021)
This research aims to know the impact of price and services toward customer satisfaction in culinary business and to know the perceptions of the customers to the food and beverages provided in the culinary business in Berastagi, The Regency of Karo. The technique of data collections is done by distributing questionnaires and interviewing the business owners, then the questionnaires area analysed using quantitative approach by describing the results of the analysis. This is the causality research that analyzes how a variable impacts other variable. The numbers of the respondents for this research are 100 persons, where they are all the customers of the restaurants, coffee shops, and cafes. The is also explorative research where the researchers do direct surveys to then location of research to get the data and informations needed, both primary and secondary data. The research shows that the pricing policy of food and beverages impacts toward the customer satisfaction for 76,40 % and it is strong category. The services given to the customers impacts toward customer satisfaction for 58,50 and it is fair category. There are two aspects perceived over customer expectations, they are the variations of food and the freshness of food and beverages. Then the aspects of food and beverages tastes and the availability of menu lists are perceived as their expectations, while the the portions and the originality of the ingredients are in good perceptions. The uniqueness of the food tastes got bad perceptions by the customers.